Tolerability and outcome of once weekly liposomal amphotericin B for the prevention of invasive fungal infections in hematopoietic stem cell transplant patients with graft-versus-host disease. (April 2016) - Luu Tran, Huong; Mahmoudjafari, Zahra; Rockey, Michelle; Henry, Dave; Grauer, Dennis; Aljitawi, Omar; Abhyankar, Sunil; Ganguly, Siddhartha; Lin, Tara; McGuirk, Joseph
Background: Invasive fungal infections remain problematic in immunosuppressed allogeneic stem cell transplant recipients and the use of corticosteroids for the treatment of graft-versus-host-disease can increase the risk threefold. Although antifungal prophylaxis has been shown to decrease the incidence of infection, the optimal antifungal prophylactic regimen in this patient population has yet to be identified. Since early diagnosis of fungal infections might not be possible and the treatment of established fungal infections might be difficult and associated with high infection-related mortality, prevention has become an important strategy in reducing overall morbidity and mortality. While triazoles are the preferred agents, some patients are unable to tolerate them and an alternative drug is warranted. Objectives: To assess the tolerability of once weekly liposomal amphotericin B as a prophylactic strategy in patients undergoing stem cell transplantation by evaluating any adverse events leading to its discontinuation. In terms of efficacy, to also compare the outcome and incidence of invasive fungal infections in patients who received amphotericin B, triazoles, and echinocandins. Results: A total of 101 allogeneic transplant recipients receiving corticosteroids for the treatment of graft-versus-host-disease and antifungal prophylaxis were evaluated from August 2009 to September 2012. Liposomal amphotericin B 3 mg/kg intravenous once weekly was found to be well tolerated. The incidence of invasive fungal infections was 19%, 17%, and 7% in the liposomal amphotericin B, echinocandin, and triazole groups, respectively. Two deaths occurred in the liposomal amphotericin B group and one death occurred in the echinocandin group. None of the deaths were fungal infection related. Conclusion: Antifungal prophylaxis with liposomal amphotericin B was well tolerated, but the incidence of invasive fungal infections in patients receiving liposomal amphotericin B was higher than other antifungal agents in this study. The optimal dose and schedule of liposomal amphotericin B for antifungal prophylaxis in this patient population are still not known and considering its broad spectrum activity, prospective trials in comparison to triazoles are warranted.